Formação docente : do debate da inovação às mudanças paradigmáticas no contexto dos paradigmas educacionais vigentes - Maldonado, Luciene (2020)
Throughout the formative years as a student, the concerns that emerged from the experiences and the trajectory in which the educational path was being built, produced an unsettling curiosity about the future of Education in the 21st century. The present thesis analyzes the reasons that impel higher education institutions and teachers to redefine and / or re-signify their training, practices and theories in undergraduate courses. The explored research methodology was the bibliographic study and analysis of research content between the years 2008 to 2018 of Thesis and Dissertations produced in several higher education institutions. I sought to understand the aspects applicable to changes in traditional and dominant paradigms in regard to the education in undergraduate courses. In same sense, I observed the relevance in the discourses about differentiated pedagogical practices related to innovations in the Education and teaching and the necessity for an academic transformation in the practices and in the formation of the future teacher, with a view to differentiated projects that intend to given new meanings to the Education. In the final considerations, were showed an analysis of master’s dissertations that have compromise with the changes in teaching practices, in other words, a commitment to the Doing. This works demonstrated their Praxis with look to a more dynamic teaching in the sense of a more integrated formation. All analyzed works have a spread of concepts and ties with the academic theories, also the interlacement of educational paradigms - showing in theory o - Way of Doing.